ANALISIS FAKTOR YANG MEMENGARUHI KEJADIAN KEKURANGAN ENERGI KRONIS (KEK) PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS LANGSA KOTA KOTA LANGSA PROVINSI ACEH TAHUN 2016 - Diza Fathamira Hamzah (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2017)
ABSTRACT Chronic energy deficiency in pregnant women is a problem that still happens till this day. Chronic energy deficiency in pregnant women can be impact to the mother’s health during pregnancy, labor and health condition of child who will be born. The research used an observational method with cross sectional design which aims to determine the factors that affecting the incidence of chronic energy deficiency in pregnant women in Langsa Kota community health center’s region. The population were 167 pregnant women and 42 of them were used as the study sample obtained by cluster sampling technique .The data were collected by using questionnaires and measurement of upper arm circumference. The factors which affecting to the chronic energy deficiency incidence analysed by using multiple logistic regression test with confidence level 95%. The result showed that income is the most significant variable than other variable (p-value 0,208) with odds ratio value 3,155. The result indicated that pregnant women who have income below the provincial minimum wage are at risk of 3,155 times suffering chronic energy deficiency than those who do not. It is recommended for local government attention to expand a saving and loan cooperative program in order to increase family income.Keywords : Incident of Chronic Energy Deficiency, The Dominant Factor Affecting